(untitled) (Indian Journal of Child Health, 2018)
Tuberculosis is a significant public health concern affecting people of all age groups in developing countries. Agranulocytosis and pancytopenia occurring in adult tuberculosis patients taking antitubercular therapy (ATT) are well known. In contrast, only a couple of reports are available in the literature documenting pancytopenia in children with tuberculosis receiving ATT. These have reported pancytopenia secondary to disseminated tuberculosis presenting as hemophagocytosis or due to drug-induced systemic lupus erythematosus. However, clinically significant pancytopenia in the absence of hemophagocytosis and secondary lupus along with concurrent hepatitis leading to congestive cardiac failure in pediatric age group as witnessed in the index patient occurring due to ATT has not been reported previously. This child developed severe anemia presenting as congestive cardiac failure requiring multiple packed red blood cell transfusions. This case reinforces the need for regular hematological and liver function test monitoring in children receiving ATT so as to prevent the development of complications such as congestive cardiac failure.